2021
DOI: 10.4149/neo_2020_200923n1010
|View full text |Cite
|
Sign up to set email alerts
|

Magnolol suppressed cell migration and invasion and induced cell apoptosis via inhibition of the NF-κB signaling pathway by upregulating microRNA-129 in multiple myeloma

Abstract: Multiple myeloma (MM) is incurable cancer in the blood system. Magnolol is an effective component against various cancers. This study tried to investigate the effect and mechanism of magnolol on MM via regulating miR-129. Human normal plasma cells (nPCs) and MM cells U266 and LP1 were used in this study, accompanied by treatment of magnolol. The miR-129 inhibitor was transfected into U266 and LP1 cells during experiments. Cell viability was detected by Cell Counting Kit-8 assay. Cell migration and invasion wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Moreover, several studies have revealed that JNK1/2 plays an anti-tumor role in oral cancer and emphasizes its positive role in apoptosis [34][35][36]. Numerous studies have also reported that magnolol inhibits cancer progression [14] or induces apoptosis [13,37] by regulating multiple cellular signaling pathways. Su et al reported that magnolol induces colorectal cancer apoptosis through both extrinsic/intrinsic pathways via PKCδ and NF-κB signaling [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, several studies have revealed that JNK1/2 plays an anti-tumor role in oral cancer and emphasizes its positive role in apoptosis [34][35][36]. Numerous studies have also reported that magnolol inhibits cancer progression [14] or induces apoptosis [13,37] by regulating multiple cellular signaling pathways. Su et al reported that magnolol induces colorectal cancer apoptosis through both extrinsic/intrinsic pathways via PKCδ and NF-κB signaling [14].…”
Section: Discussionmentioning
confidence: 99%
“…Su et al reported that magnolol induces colorectal cancer apoptosis through both extrinsic/intrinsic pathways via PKCδ and NF-κB signaling [14]. Moreover, in multiple myeloma, magnolol induced cell apoptosis and inhibited cell migration by upregulating miR-129 and inhibiting NF-κB pathway activation [13]. Chen et al demonstrated that magnolol induced apoptosis by activating the ERK1/2 and p38 pathways in esophagus cancer KYSE150 cells [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NF-κB is activated by the phosphorylation-induced degradation of IκBs, which facilitates the dissociation of NF-κB from IκB family proteins in cytoplasm [ 67 ]. In various cancer types, magnolol exerted the inhibitory effect on NF-κB activity, which is demonstrated by studies of breast cancer [ 15 ], cholangiocarcinoma [ 17 ], colon cancer [ 23 ], liver cancer [ 34 , 36 ], lung cancer [ 39 ], myeloma [ 44 ], ovarian cancer [ 48 ] and skin cancer [ 57 ] ( Table 1 and Figure 2 ). For the majority of cases, the inactivation of NF-κB signaling induced by magnolol was to block the phosphorylation of IκBα and/or p65 subunit of NF-κB.…”
Section: Magnolol Inhibits Nf-κb Signalingmentioning
confidence: 97%
“…In recent years, magnolol has exhibited the antiproliferative property against various cancer types. Magnolol effectively inhibited tumor cell growth in bladder cancer [ 13 , 14 ], breast cancer [ 15 , 16 ], cholangiocarcinoma [ 17 ], colon cancer [ 18 , 19 , 20 , 21 , 22 , 23 ], esophagus cancer [ 24 ], fibrosarcoma [ 25 ], gallbladder cancer [ 26 ], gastric cancer [ 27 ], glioblastoma [ 28 , 29 , 30 , 31 , 32 ], leukemia [ 25 ], liver cancer [ 21 , 33 , 34 , 35 , 36 ], lung cancer [ 37 , 38 , 39 , 40 ], lymphoma [ 41 ], melanoma [ 25 , 42 , 43 ], myeloma [ 44 ], oral carcinoma [ 45 , 46 ], osteosarcoma [ 47 ], ovarian cancer [ 48 ], pancreatic cancer [ 49 ], prostate cancer [ 50 , 51 , 52 , 53 ], renal cancer [ 54 , 55 ], skin cancer [ 56 , 57 ] and thyroid cancer [ 58 ] (…”
Section: Magnolol Inhibits Proliferation and Growthmentioning
confidence: 99%